2015
DOI: 10.1007/s12035-015-9236-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Sleep Deprivation-Induced Blood-Brain Barrier Breakdown and Brain Dysfunction are Exacerbated by Size-Related Exposure to Ag and Cu Nanoparticles. Neuroprotective Effects of a 5-HT3 Receptor Antagonist Ondansetron

Abstract: Military personnel are often subjected to sleep deprivation (SD) during combat operations. Since SD is a severe stress and alters neurochemical metabolism in the brain, a possibility exists that acute or long-term SD will influence blood-brain barrier (BBB) function and brain pathology. This hypothesis was examined in young adult rats (age 12 to 14 weeks) using an inverted flowerpot model. Rats were placed over an inverted flowerpot platform (6.5 cm diameter) in a water pool where the water levels are just 3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 67 publications
(151 reference statements)
2
11
0
Order By: Relevance
“…Sleep participates in the neural biological regulation by facilitating the elimination of metabolites along the BBB (55). As in severe stress, sleep deprivation impairs BBB function and induces brain pathology (21). Similarly, our study also showed that BBB permeability was significantly increased in mice with sleep deprivation induction, suggesting the vital effect of sleep deprivation on the BBB.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Sleep participates in the neural biological regulation by facilitating the elimination of metabolites along the BBB (55). As in severe stress, sleep deprivation impairs BBB function and induces brain pathology (21). Similarly, our study also showed that BBB permeability was significantly increased in mice with sleep deprivation induction, suggesting the vital effect of sleep deprivation on the BBB.…”
Section: Discussionsupporting
confidence: 69%
“…The sleep deprivation model was induced using an inverted flowerpot in a water tank (21). Briefly, sleep deprived (SD, n = 9) mice were placed on an inverted flowerpot (platform of 1.1 cm diameter) surrounded by a water-filled chamber of Plexiglas.…”
Section: Establishment Of the Sleep Deprivation Modelmentioning
confidence: 99%
“…In concordance with the above mentioned research inferences, the present study too reported that Panax quinquefolius (GIN) treatment for 8 days in sleep deprived animals significantly attenuated the anxiogenic like behavior, oxidative stress, mitochondrial dysfunction, serum corticosterone and pro-inflammatory marker (TNF-α) levels as well as minimized histological neuronal changes as compared to the sleep deprived vehicle treated animals. Although GABA is known to be a primarily involved in consequences of SD, but sleep research in recent times has also pointed toward significant alterations in 5-HT neurotransmission as well as neurochemical metabolism (under the control of molecules like 5-hydroxytryptamine transporter, 5-HTT and Glycogen synthase kinase 3-β) as a direct consequence of SD (Benedetti et al, 1999 , 2012 ; Monti et al, 2011 ; Zant et al, 2011 ; Elmenhorst et al, 2012 ; Sharma et al, 2015 ). Also, 5-HT receptor antagonists have recently be classified for their promising role against SD-induced brain dysfunctions (Youngblood et al, 1999 ; Morairty et al, 2008 ) affirming that the secondary neurological debilities manifested as a direct concern of SD can also be accredited to altered 5-HT neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mice undergoing chronic sleep restriction have decreased expression and function of GLUT1, impaired tight junction expression and BBB transport, and suppressed vascular reactivity with reduced inducible nitric oxide synthase (iNOS), endothelial NOS (eNOS) and ET-1 [147]. Also, rats subjected to sleep deprivation exhibited BBB breakdown and leakage [148]. …”
Section: Vascular Risk Factors Lifestyle and Environmentmentioning
confidence: 99%
“…Experimental studies in rodents have shown that silver, copper or aluminum/aluminum oxide nanoparticles disrupt the BBB, reduce the expression of endothelial tight junctions, decrease CBF, and induce edema, synaptic dysfunction and neurodegeneration [157160]. Interestingly, silver and copper nanoparticle exposure exacerbated BBB dysfunction when accompanying sleep deprivation [148] or diabetes [158]. …”
Section: Vascular Risk Factors Lifestyle and Environmentmentioning
confidence: 99%